If (a+2b+c),(a-c) and (a-2b+c) are in continued proportion, prove that b is the mean proportion between a and c

2 Answers | Add Yours

Top Answer

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

It is given that (a+2b+c),(a-c) and (a-2b+c) are in continued proportion.

This gives (a + 2b + c)/(a - c) = (a - c)/(a - 2b + c)

=> (a + 2b + c)(a - 2b + c) = (a - c)^2

=> (a + c)^2 - 4b^2 = (a - c)^2

=> a^2 + c^2 + 2ac - 4b^2 = a^2 + b^2 - 2ac

=> 4ac = 4b^2

=> ac = b^2

=> b/a = c/b

This proves that b is the mean proportion between a and c or b/a = c/b.

giorgiana1976's profile pic

giorgiana1976 | College Teacher | (Level 3) Valedictorian

Posted on

For b to be the mean proportion of a and c, the following relation has to b verified:

b = sqrt(a*c)

We'll replace b by (a-c) and the product a*c by the product (a+2b+c)*(a-2b+c)

We notice that the product (a+2b+c)*(a-2b+c) returns the difference of two squares:

(a+2b+c)*(a-2b+c) = (a+c)^2 - (2b)^2

The relation that has to be verified is:

(a-c) = sqrt[(a+c)^2 - (2b)^2]

We'll raise to square both sides:

(a-c)^2 =(a+c)^2 - (2b)^2

We'll expand the binomials:

a^2 - 2ac + c^2 = a^2 +2ac + c^2 - 4b^2

We'll eliminate a^2 + c^2:

- 2ac = 2ac - 4b^2

But b^2 = ac

- 2ac = 2ac - 4ac

-2ac = -2ac

Since the LHS = RHS, therefore b is the mean proportion between a and c, if (a+2b+c),(a-c) and (a-2b+c) are in continuous proportion.

We’ve answered 318,915 questions. We can answer yours, too.

Ask a question